Effectiveness of Project-Based Learning in Developing Critical Thinking Skills among Secondary School Students - Sohail, Sidra; Iqbal, Tanveer; Munawar, Sumaira (Pakistan Languages and Humanities Review, 2025)
This research examines how project-based learning (PBL) influences the development of critical thinking skills in secondary school students. Using a mixed-methods design, the study integrates quantitative pre-test and post-test evaluations with qualitative observations and interviews for a thorough assessment of PBL's effects. Over a 12-week period, 250 students from 50 public schools engaged in PBL activities focused on inquiry-based learning and collaborative problem-solving. The qualitative analysis identified themes of heightened student engagement, improved collaborative learning, and evident critical thinking behaviors. These findings indicate that PBL is an effective method for enhancing critical thinking in elementary education. Recommendations include incorporating PBL into the curriculum, offering professional development for educators, and ensuring all students have access to PBL opportunities.